Report of the Explorations for a Route for the Pacific Railroad 1854 - E. G. Beckwith (Symphony in the Flint Hills, 2013)
A description of Kansas land by Lt. E.G. Beckwith after his exploration of the area to discover a desierable route for the Pacific Railroad.
Keywords: exploration; travel; westward; western; railroad; rail; train; route; Pacific Railroad; timeline; survey; settlers; fuel; Fort Riley; Major Ogden; Smokey Hill; river; junction